Are We Passing on Violence to the Next Generation?: Gender Norms and Gender-based Violence Attitudes among Early Adolescents in Indonesia - Mahendra, I Gusti A A; Pinandari, Anggriyani Wahyu; Choiriyah, Ifta; Wilopo, Siswanto Agus (Kesmas, 2021)
Intensification of gender norms during puberty affects adolescents’ perceptions and behavior related to violence. This study examined the association between gender norms and gender-based violence (GBV) among early adolescents considering socio-ecological variables using cross-sectional data from 3,618 Indonesian Global Early Adolescent Study pupils. Chi square tests with simple and multiple logistic regression analyses examined how different factors' levels predict GBV. Among boys, GBV attitudes were found high (53%). Furthermore, they also had high heteronormative expectations, threatened feelings, experiences of violence, porn access, and 5+ adverse childhood experiences (ACEs). Logistic regression results revealed that adolescent boys having one or two scores of gender norms at the above-median are 1.3 times more likely to commit GBV and even 2.2 times higher if all were above median [AOR (CI) = 1.3(1.1-1.6); 2.2 (1.7 2.8)], respectively. Boys, having 5+ ACEs, and stronger endorsement on heteronormative relationships were also more likely to commit GBV [AOR (CI) = 1.5 (1.3-1.7); 1.5 (1.2-1.9); 1.5 (1.3-1.7)], respectively. This research concluded that unequal gender norms intensified during puberty strongly correlate to attitudes towards GBV among early adolescents. Strengthening the individual aspects by providing a more conducive environment, such as comprehensive sexual education at school, is essential to prevent GBV.